"SLAMETHAN ASSÎR" as A Media of Harmonization between Individual Happiness and Social Peace - Arifin, Samsul (Proceedings of Annual Conference for Muslim Scholars, 2022)
The kiai of the Besuki Residency in the past, had local wisdom in carrying out social harmonization to achieve mutual happiness. One of them is through "Slamethan Assîr" which is carried out by the community so that they can grow and develop in their careers. This study aims to understand the meaning of achieving happiness and prosperity in life through "Slamethan Assîr" and its implementation in career development, from the perspective of self-concept theory of career development. This research uses the ethnographic method. The results of this study indicate that "Slamethan Assîr" means as a guide that a career must contain the value of worship, hoping for blessings for the family, and giving charity to maintain harmony with neighbors. Career development is a process of developing self-concept; self-quality and competence and paying attention to the environmental context. The standard of career success is to feel prosperous and happy with family, friends, or neighbors and must be in line with the pleasure of Allah. So they will avoid corrupt, fraudulent, and other heinous acts. This research is useful for the development of the psychology of entrepreneurship and career